Artificial intelligence as an information security tool - Rostyslav Artym; Shulha Tetyana (Закарпатський угорський інститут імені Ференца Ракоці II, 2024)
Abstract. In today’s world, the rapid advancement of information technologies, when not adequately embraced by society, presents a significant challenge. This directly impacts the information security of both the state and major entities such as international corporations. Artificial intelligence (AI) has become a potent tool in discerning and addressing issues associated with cyberattacks and information threats, with information security being one of its key aspects. AI's domain lies in automating information protection processes and countering evolving threats at increasingly sophisticated levels. The purpose of this paper is to study the role of artificial intelligence in ensuring information security, namely, to provide examples of the effective use of AI to eliminate constant threats in the field of information security. The most critical areas of artificial intelligence usage for ensuring security in the information space include attack detection or prediction, analysis of information data, intelligent authentication methods, self-learning, and adaptation.
Keywords: Artificial intelligence; information security